2023
DOI: 10.1186/s40001-023-01181-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics analysis of DNA replication-associated primase polymerase (PRIMPOL) in pan-cancer: a potential target for prognosis and immune response

Abstract: Background It is critical to understand the mechanisms of human cancers in order to develop the effective anti-cancer therapeutic strategies. Recent studies indicated that primase polymerase (PRIMPOL) is strongly associated with the development of human cancers. Nevertheless, a systematic pan-cancer analysis of PRIMPOL remains to be further clarified. Method Comprehensive multi-omics bioinformatics algorithms, such as TIMER2.0, GEPIA2.0 and cBioPor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The activity of PrimPol needs to be tightly regulated to prevent excessive repriming in order to avoid accumulation of mutations in the newly synthesized DNA, which can promote tumorigenesis. Indeed, PrimPol has been found to be upregulated in various cancers including glioblastoma multiforme and kidney renal clear cell carcinoma ( 69 ), highlighting the importance of a balanced PrimPol activity to limit excessive repriming while promoting cell survival. To date, the mechanism regulating PrimPol repriming activity remains largely elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of PrimPol needs to be tightly regulated to prevent excessive repriming in order to avoid accumulation of mutations in the newly synthesized DNA, which can promote tumorigenesis. Indeed, PrimPol has been found to be upregulated in various cancers including glioblastoma multiforme and kidney renal clear cell carcinoma ( 69 ), highlighting the importance of a balanced PrimPol activity to limit excessive repriming while promoting cell survival. To date, the mechanism regulating PrimPol repriming activity remains largely elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency in PrimPol might be associated with ophthalmological diseases (Kasamo et al 2020;Yuan et al 2020;Haarman et al 2022;Yang et al 2023;Cai et al 2019), altered response to DNA damage and chemotherapy (Quinet et al 2019), increased toxicity of retroviral nucleotide analog therapy (Duong et al 2020) as well as increased cancer suspensibility (Deng et al 2023). Deletions of PRIMPOL were found to be common for breast cancer (Ciriello et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that disfunction of PrimPol contributes to the development of some human diseases, such as hereditary mitochondrial pathologies (e.g., ophthalmic diseases and even muscular dystrophies) (Kasamo et al 2020;Zhao et al 2013;Yuan et al 2020). Comprehensive bioinformatic pan-cancer analysis revealed that aberrant PRIMPOL expression or altered protein structure in different types of cancers possibly affect clinical prognosis, cell invasion and anti-tumor immune response (Deng et al 2023). According to the TCGA PanCancer Atlas Studies (cBioPortal), 72 somatic mutations of PRIMPOL gene carrying 59 missense mutations were identified in cancer patients (Cerami et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency in PrimPol might be associated with ophthalmological diseases (Kasamo et al 2020; Yuan et al 2020; Haarman et al 2022; Yang et al 2023; Cai et al 2019), altered response to DNA damage and chemotherapy (Quinet et al 2019), increased toxicity of retroviral nucleotide analog therapy (Duong et al 2020) as well as increased cancer suspensibility (Deng et al 2023). Deletions of PRIMPOL were found to be common for breast cancer (Ciriello et al 2015).…”
Section: Discussionmentioning
confidence: 99%